Pemetaan dakwah di Negeri Johor: kajian lokasi, metodologi & pengaplikasiannya di Skudai, Kulai, Pasir Gudang dan Johor Bahru - Mustari, Mohd. Ismail; Muhammad, Azhar; Mohd Noor, Sulaiman Shakib; Mohamed, Ahmad Kilani; Abdullah, Abdul Hafiz; Basiron, Bushrah; Jasmi, Kamarul Azmi; Marni, Nurazmallail (Universiti Teknologi Malaysia, 2006)
Dakwah is the most important medium in spreading the Islamic teaching. Therefore it is important to choose appropriate methodologies in order to make the dakwah more effective towards producing an ideal and competitive Muslim society. This research is an attempt to study the methods and application of dakwah applied in four specific areas in Johor i.e. Skudai, Kulai, Pasir Gudang and Johor Bharu. In collecting the data a sample of 135 respondents from these four areas was selected. A set of questionnaires contains of 135 questions with Î± = 0.803 was used to the respondents and the data were analyzed descriptively by using SPSS (Statistical Package for The Social Sciences) 14.0 version. The findings of this research show that; four methods of dakwah were actively employed in these areas are: 1)Quranic programs 2)lecturer programs 3)hajj, zakat and fasting programs 4)community programs. The respondents strongly agreed about the important of sound methodologies used by the dut and good coordination and management of dakwah activities in order to make the dakwah more effective in their community. Majority of the respondents did not comfortable with the dakwah approaches used by the jemaah groups and the tabligh groups. Finally, the study found the lack of dakwah activities or programs especially for children and teenagers in these areas.